Strategi Peningkatan Kapasitas Modal Sosial dan Kualitas Sumber Daya Manusia Pendamping Pembangunan Pertanian - Sjafri Mangkuprawira (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2010)
EnglishBased on the Human Development Index (HDI) figures, the Indonesian welfare level show that the community development process must be continuously carried out. The most important elements in the successful achievement of community development especially in rural community to support agricultural development are natural capital, technology, institutional, human capital, and social capital. The elements of social capital in this respect are mutual trustworthy on fellow members of the community, social empathy, social cohesion, social awareness, and collective cooperation. This paper examines the significance of social capital in agricultural development, as well as how the strategy to strengthening co-utilization and community development. Through a review of some study results on the role of facilitator in community development, strengthening social capital is required in the development community, particularly through the assistantship or mentoring process. Facilitators especially extension workers are needed in community development because of their function as problem analyst, group supervisor, trainer, innovator, and liaison officer. The principles of operation are (1) working group, (2) continuity, (3) self-reliance, (4) unity of target audiences, (5) growth of mutual trust, and (6) continuous learning process. In addition, the assistantship program is highly considered as an activity enabling the optimum empowerment of the poor. For an optimum role of technical assistant, the development of quality human resources is required through participatory training-based education and development of assistantship forum. IndonesianDerajat kesejahteraan rakyat Indonesia dilihat dari angka Indeks Pembangunan Manusia membuktikan bahwa proses pengembangan masyarakat harus tetap dilaksanakan secara terarah dan bersinambung. Unsur terpenting dalam capaian keberhasilan pengembangan masyarakat khususnya di wilayah perdesaaan untuk mendukung pembangunan pertanian adalah modal alam, teknologi, kelembagaan, modal manusia, dan modal sosial. Unsur modal sosial yang dimaksud diantaranya adalah saling percaya pada sesama anggota masyarakat, empati sosial, kohesi sosial, kepedulian sosial, dan kerja sama kolektif. Makalah ini ditujukan untuk mengkaji arti penting modal sosial dalam pembangunan pertanian, serta bagaimana strategi pemanfaatan dan penguatan pendamping (khususnya penyuluh pertanian) dalam pengembangan masyarakat. Melalui review dari beberapa hasil kajian terhadap peran pendamping dalam pengembangan masyarakat, penguatan modal sosial sangat dibutuhkan dalam pengembangan masyarakat, khususnya melalui proses pendampingan. Penyuluh pertanian sangat dibutuhkan dalam pengembangan masyarakat karena mempunyai fungsi sebagai analis masalah, pembimbing kelompok, pelatih, inovator, dan penghubung. Prinsip kerja pengembangan masyarakat mendukung pembangunan pertanian melalui pendampingan adalah: (1) kerja kelompok, (2) keberlanjutan, (3) keswadayaan, (4) kesatuan khalayak sasaran, (5) penumbuhan saling percaya, dan (6) pembelajaran bersinambung. Disamping itu, pendampingan merupakan kegiatan yang diyakini mampu mendorong terjadinya pemberdayaan masyarakat miskin secara optimal. Agar pendamping dapat berperan optimum maka dibutuhkan pengembangan mutu sumber daya manusianya melalui pelatihan partisipatif berbasis pendidikan orang dewasa dan pengembangan forum pendampingan.